2011
DOI: 10.1097/icl.0b013e3182254e7d
|View full text |Cite
|
Sign up to set email alerts
|

Contact Lens Characteristics and Contrast Sensitivity of Patients With Keratoconus

Abstract: Most of our patients were managed conservatively with contact lenses, and keratoconus design RGP lenses were the most common type fitted. Good VA can be achieved, but patients with keratoconus may still experience a reduction in contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
4
7
0
Order By: Relevance
“…Although mean BCVA was improved by the Twinbel bevel toric compared with that achieved with the previous lens, the small number of subjects in the present study means that further studies are needed to confirm that this lens can to improve the quality of vision including BCVA. Contrast sensitivity was not significantly improved by the Twinbel bevel toric, which is consistent with the results of previous studies with RGP lenses in keratoconus [26][27][28].…”
Section: Discussionsupporting
confidence: 94%
“…Although mean BCVA was improved by the Twinbel bevel toric compared with that achieved with the previous lens, the small number of subjects in the present study means that further studies are needed to confirm that this lens can to improve the quality of vision including BCVA. Contrast sensitivity was not significantly improved by the Twinbel bevel toric, which is consistent with the results of previous studies with RGP lenses in keratoconus [26][27][28].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies report that although good visual acuity may be achieved with RGP lenses on irregular corneas, visual quality could be decreased [32,33]. The outcomes of this study show that visual acuity improved significantly, that similar values to previous studies were achieved in which the same CScL were fitted in keratoconic eyes without ICRS implants [30] and on irregular corneas of post-LASIK eyes [29].…”
Section: Discussionsupporting
confidence: 86%
“…For instance Cox et al [18] reported in their study that soft contact lenses may induce spherical aberrations which could be the reason of contrast sensitivity loss in 6 mm- sized pupils, Grey et al [19] reported reductions in contrast sensitivity in the previous soft contact lens wearers whose lenses were made of hydrogel material. Also Wei et al [20] reported that rigid gas permeable lenses improved visual acuity significantly but contrast sensitivity was reduced in keratokonic patients. We have found a significant increase in low- contrast sensitivity values after contact lens application in both groups However when we compared on-eye and off-eye results there were no significant differences between the two groups and after contact lens fitting the contrast sensitivity values were sufficient and satisfactory for both goups.…”
Section: Discussionmentioning
confidence: 99%